Avatars of an investigation at the frontiers: Reflections on the ethnographic process in popular economy organizations (Polis (Santiago), 2024)
In this paper I reflect on the problems that can arise in the ethnographic process based on my experience in the field as a researcher and at the same time as a militant of a popular economy movement in the province of Jujuy, Argentina. Returning to the main discussions about the ethnographic method and presenting the difficulties in the field in light of my personal involvement, I propose possible solutions to multiple crossroads that arise in the field of study, such as militant research and the active participation of those who are part of it research based on the revaluation of their knowledge and their political praxis.
Keywords: Ethnographic method; popular economy; reflexivity; activist research; frontiers